Warning Time Analysis From SEP Simulations of a Two‐Tier REleASE System Applied to Mars Exploration. Issue 4 (16th April 2020) - Posner, A.; Strauss, R.D.
Abstract: The sudden exposure to energetic protons from solar energetic particle (SEP) events beyond the Earth's magnetosphere and en route to and from Mars can, in extreme cases, lead to acute radiation sickness, an impairing, mission‐endangering condition for astronauts. Timely warnings of their impending occurrence may significantly reduce radiation exposure by allowing astronauts sufficient time to move to a radiation shelter. The Relativistic Electron Alert System for Exploration (REleASE) has been developed to provide such early warnings for the Earth‐Moon system by exploiting the time difference of the arrival of SEP electrons and ions at 1 AU. This study explores the effectiveness of REleASE in a scenario that assumes a two‐element system, one placed at Earth‐Sun L1 and the other at Mars‐Sun L1. This system would exploit the Hohmann‐Parker effect, the circumstance that a spacecraft remains close to the heliospheric magnetic field lines that connect Earth and/or Mars with the Sun while in the Hohmann transfer orbit. We investigate whether the two‐element REleASE system would provide advance warnings for all phases of a mission to and from Mars. In the absence of adequate long‐term SEP measurements beyond Earth orbit, we employ 2‐D modeling of SEP injection and transport for SEP exposure scenarios, in which the best magnetic connections and thus most rapid flux increases of protons occur at exploration vehicle. We show the relative timing of alert occurrence and arrival of harmful ions at the spacecraft throughout a round‐trip human mission to Mars. Key Points: Effectiveness of a two‐tier Relativistic Electron Alert System for Exploration was analyzed with 2‐D solar particle event modeling System would protect astronauts from sudden solar particle radiation exposure during entire two‐way transit between Earth and Mars A two‐tier warning system that exploits the Hohmann‐Parker effect would be placed at Earth‐Sun L1 and Mars‐Sun L1 Lagrange points